Kombinasi Aromaterapy Jasmine Sambac dan Loving Yoga terhadap Disfungsi Seksual pada Akseptor KB Suntik DMPA - Antri Ariani; Intan Yusita; Dewi Nurlaelasari (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
One of the side effects of the 3-Month Injectable KB is impaired sexual function caused by the high level of the hormone progesterone, resulting in vaginal drying, which causes pain during sexual intercourse, which can lead to a decrease in sexual desire or dysfunction in women. Jasmine Sambac is an effective and gentle way to promote a healthy body and for relaxation. Loving yoga is a type of yoga developed by researchers, with a focus on Kegel exercises and pelvic muscles that function to increase blood flow, so that the body feels relaxed which can increase libido in sexual intercourse. The purpose of this study was to identify the effect of the combination of Aromatherapy Jasmine Sambac and Loving Yoga on sexual dysfunction in DMPA injection family planning acceptors. The research method used is a quasi-experimental approach with a one group pre-post test design approach. Measurement of pre-test and post test was carried out using the FSFI (Female Sexual Function Index) instrument. The results showed that jasmine sambac aromatherapy and loving yoga had a significant effect on increasing the total libido, including its 6 aspect domains, on DMPA injection acceptors.